Tinjauan terhadap Kekuatan Eksekutorial Putusan PTUN Pasca Undang-Undang Nomor 51 Tahun 2009 - Muhammad Mujab Nabil; Zahran Qolbi Salim; Eiffeliqa Torriq Fatima Putrinindra; Moh. Imam Gusthomi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Law Number 51 of 2009 represents a pivotal milestone in strengthening the authority of the Indonesian Administrative Court (PTUN), particularly regarding the executorial aspects of its decisions, which were previously considered weak and insufficient in providing adequate legal protection for the public. This study aims to examine and analyze the executorial power of PTUN decisions following the enactment of the regulation, with a focus on the effectiveness of decision enforcement, the obstacles encountered, and the implications for governance based on the principles of the rule of law. Employing a normative juridical approach supported by analyses of literature, legislation, and selected court decisions, this research demonstrates that Law 51/2009 has brought significant progress, especially through provisions requiring administrative officials to comply with court rulings, the introduction of administrative sanctions, and the application of dwangsom as a coercive measure. However, its effectiveness remains suboptimal due to several persistent challenges, including weak oversight of officials who fail to implement decisions, the limited application of sanctions in practice, and a bureaucratic culture that tends to be unresponsive to judicial authority. Additionally, disharmony among sectoral regulations and insufficient inter-agency coordination further hinder the executorial function of PTUN.